Identification of Ethnomathematics in Wat Arun “Temple of Dawn” in Bangkok, Thailand - Halim, Erwin Ardianto; Darmayanti, Tessa Eka (Local Wisdom Jurnal Ilmiah Kajian Kearifan Lokal, 2025)
This qualitative descriptive research was conducted to identify ethnomathematics concepts in Wat Arun "Temple of Dwan" in Bangkok, Thailand using the ethnographic approach. The purpose was to explore and examine the mathematical elements or concepts as well as meaning contained in the geometric patterns of temple. The process involved describing the motif associated with temple based on certain categories using the data retrieved from documentation, observation, and literature review. The results showed that mathematical and the geometric concepts such as triangles, squares, and rhombus were depicted in the geometric and floral motifs, offering compelling evidence of the involuntary implementation of mathematics in traditional motifs. Furthermore, these results can also be applied as a reference to develop mathematics teaching materials and interior design or architecture courses based on local wisdom.